2022
DOI: 10.1038/s41586-022-04736-8
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale imaging of phonon dynamics by electron microscopy

Abstract: Spatially resolved vibrational mapping of nanostructures is indispensable to the development and understanding of thermal nanodevices1, modulation of thermal transport2 and novel nanostructured thermoelectric materials3–5. Through the engineering of complex structures, such as alloys, nanostructures and superlattice interfaces, one can significantly alter the propagation of phonons and suppress material thermal conductivity while maintaining electrical conductivity2. There have been no correlative experiments … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 46 publications
0
33
0
Order By: Relevance
“…To resolve this issue, we map the Li distributions by probing Li-O vibrations. We employ a state-of-the-art vibrational EELS technique enabled by high energy resolution monochromation that has facilitated the spectroscopy of vibrational excitations at the nanometer 53,54 and even atomic scales 52,55 . We employ a dark field vibrational EELS (DF VibEELS) beam-detector geometry (Supplementary Fig.…”
Section: Lstz075 Gb Composition and Its Effect On Ionic Conductivity ...mentioning
confidence: 99%
“…To resolve this issue, we map the Li distributions by probing Li-O vibrations. We employ a state-of-the-art vibrational EELS technique enabled by high energy resolution monochromation that has facilitated the spectroscopy of vibrational excitations at the nanometer 53,54 and even atomic scales 52,55 . We employ a dark field vibrational EELS (DF VibEELS) beam-detector geometry (Supplementary Fig.…”
Section: Lstz075 Gb Composition and Its Effect On Ionic Conductivity ...mentioning
confidence: 99%
“…In parallel, other researchers measured the phonon modes in strontium titanate−calcium titanate superlattices 50 and silicon−germanium interfaces 51 to map the spatial extent of interfacial phonon modes. Recent work by Gadre et al 52 observed that abrupt Si−Ge interfaces impede the phonon propagation to a higher degree than gradual interfaces, thus explaining the decrease in the thermal conductivity at abrupt interfaces. These studies illustrate how q-EELS can experimentally probe localized interfacial phonon modes and can provide unique insights into the engineering of material interfaces for desirable electrical and thermal transport properties.…”
Section: Momentum-resolved Vibrational Eels (Q-eels)mentioning
confidence: 99%
“…In this work, we propose a novel exploitation of the momentum distribution via inelastic scatterings of the atomically confined plasmonic fields, where the energy and momentum conservation laws together govern the corresponding optical processes (Figure a). A perfect subject is to measure phonon dispersions that play an essential role in many properties, such as mechanical stabilities, electrical/thermal conductivities, , and optical transitions, in solid states. To this end, the Raman processes of a single trans -polyacetylene (t-PA) chain are taken as a proof of concept, which leads to the precise determination of all phonon branches of t-PA in the whole Brillouin zone from the Raman images for the first time.…”
mentioning
confidence: 99%